ENGLISH TEACHERS’ PERCEPTIONS AND PRACTICES OF AUTHENTIC ASSESSMENT - Aliningsih, Fitri; Sofwan, Ahmad (Universitas Negeri Semarang, 2015)
This study aimedto find the English teachers‘ perceptions and practices of authentic assessment in the pilot project schools of the 2013 curriculum in Grobogan regency. In order to achieve the objectives of the study, first, a survey was done. Then, to obtain more in-depth information about the teachers‘ perceptions and practices of authentic assessment, a case study research was conducted. In this case, interview and classroom observation were conducted. Then, the data were analyzed through reading or memoing, describing, and classifying.The study revealed that the teachers have positive perceptions towards authentic assessment as they agreed that the assessment approach is beneficial to assess students‘ progress and achievement. However, the teachers perceived insufficient time, crowded classes, exhausting and time consuming activities, and also complicated administration as the main problems in applying authentic assessment. There were no significant differences among the teachers on the way they applied authentic assessment. In this case, they preferred written and task basedassessment, performance assessment, and also classroom observation in assessing their students. Nevertheless, in some cases, they did not apply the assessment properly as they did not put the assessment principles into practices.